2011
DOI: 10.1111/j.1447-0349.2011.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Pro re nata use in a psychiatric intensive care unit

Abstract: Pro re nata (PRN) or 'as required' medication is a regular part of mental health nursing practice. This retrospective study accessed data recorded for all PRN being given to patients within an eight-bed psychiatric intensive care unit. Data from the same consecutive 4-month period from 2005 and from 2007-2009 were analysed for trends in overall rates, time of administration, and type of medication given. PRN administration was identified to each patient, but no demographic information was analysed. Results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
(106 reference statements)
0
20
0
Order By: Relevance
“…; Usher et al . ), along with unsettled behaviour, violence (Haw & Wolstencroft ), insomnia and distressing symptoms (Mullen & Drinkwater ). Environmental factors include high levels of ward acuity, staffing levels and skill mix as well as the enforcement of smoking bans in hospitals (Stewart et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Usher et al . ), along with unsettled behaviour, violence (Haw & Wolstencroft ), insomnia and distressing symptoms (Mullen & Drinkwater ). Environmental factors include high levels of ward acuity, staffing levels and skill mix as well as the enforcement of smoking bans in hospitals (Stewart et al .…”
Section: Introductionmentioning
confidence: 99%
“…) as it often precluded other interventions such as de‐escalation through the use of effective communication techniques (Bowers et al . ; Mullen & Drinkwater ; Price & Baker ). Stewart et al .…”
Section: Introductionmentioning
confidence: 99%
“…). The most frequently prescribed PRN medications are hypnotics, anxiolytics, and antipsychotics (Mullen & Drinkwater ; Srivastava ; Wright et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…), and they have had tendency to resort to PRN too easily (Baker et al . ; Hayes & Russ ; Mullen & Drinkwater ). It has been reported that professionals have the power to identify the need for PRN and patients’ views are not considered (Cutcliffe & Happell ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation